Documenting the MCMH: Development of the methodology based on GIS analysis parameters - Rodrigues, Inês Lima; Shach-Pinsly, Dalit; Porat, Idan; Amir, Or (35Th International Geographical Congress 2024, 2024)
This paper presents qualitative and quantitative analyses of middle-class mass housing (MCMH) built in Europe between 50th – 70th. We developed a methodology for documenting MCMH case studies, based on a rigorously-designed template, to create a comparative evaluation of urban and sustainable aspects that are part of the most relevant MCMH neighborhoods in Europe, aiming to identify the urban and architectural characteristics in dialogue with the concepts that define MCMH. As a result, it was possible to map more than 110 MCMH neighbourhoods spread over several cities in 30 European countries. The analysis of the data added to the templates was inserted into mapping analysis systems, the GIS (Geographical Information System), to demonstrate different perspectives on the built environment. Within this framework, a fascinating research project has been developed that is currently progressing with the exploratory research capabilities of new analytical tools, such as the integration of all case studies in GIS to achieve an original analysis based on different issues, including the distribution of uses (building typologies, open areas, green areas, parking etc.), and various statistics for all case studies. To evaluate the qualitative data, we developed a unique methodology that analysed similar aspects, diverse words, or groups of terms or notions. The analysis revealed certain common traits, such as particular repetitive characteristics which appear in many MCMH neighbourhoods and those that appear only in specific ones: walkable neighborhoods, less walkable neighbourhoods, neighborhoods connected to central areas either on foot or by car or other public transport, etc.